Disorder and Strain-Induced Complexity in Functional Materials - Kakeshita, Tomoyuki; Fukuda, Takashi; Saxena, Avadh; Planes, Antoni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book brings together an emerging consensus on our understanding of the complex functional materials including ferroics, perovskites, multiferroics, CMR and high-temperature superconductors. The common theme is the existence of many competing ground states and frustration as a collusion of spin, charge, orbital and lattice degrees of freedom in the presence of disorder and (both dipolar and elastic) long-range forces. An important consequence of the complex unit cell and the competing interactions is that the emergent materials properties are very sensitive to external fields thus rendering these materials with highly desirable, technologically important applications enabled by cross-response.
Ferroics and multiferroics -- Principles of complexity in materials physics -- Understanding glassy phenomena in materials -- Soft electronic matter -- Hysteresis and avalanches -- High resolution visualization techniques: Structural aspects -- High resolution visualization techniques: Magnetic aspects -- Strain glasses and martensites -- Defects in ferroelectrics -- First principle calculations -- Nanoscale strain textures and interfaces: Magnetic Martensites -- Neutron scattering and shuffle based transitions: Precursor phenomena in magnetic materials -- Magnetostructural coupling and magnetocaloric properties in Heusler shape-memory alloys -- Ni-Mn-X Heusler materials -- Precusor nanoscale textures in martensites and magnetic materials -- Conclusion and future directions.
Keywords: Magnetism; Materials; Materials Science; Structural Materials; Magnetism, Magnetic Materials; Ceramics, Glass, Composites, Natural Methods; Nanoscale Science and Technology; Applied and Technical Physics